Multiagent association rules mining in cooperative learning systems - Alhaj, R; Kaya, M (Springer-Verlag Berlin, 2005)
Recently, multiagent systems and data mining have attracted considerable attention in the computer science community. This paper combines these two hot research areas to introduce the term multiagent association rule mining on a cooperative learning system, which investigates employing data mining on a cooperative multiagent system. Learning in a partially observable and dynamic multiagent systems environment still constitutes a difficult and major research problem that is worth further investigation. Reinforcement learning has been proposed as a strong method for learning in multi-agent systems, So far, many researchers have proposed various methods to improve the learning ability in multiagent systems. However, reinforcement learning still has some drawbacks. One drawback is not modeling other learning agents present in the domain as part of the state of the environment. Another drawback is that even in learning case, some state-action pairs are experienced much less than others. In order to handle these problems, we describe a new action selection model based on association rules mining. Experimental results obtained on a well-known pursuit domain show the applicability, robustness and effectiveness of the proposed learning approach.
1st International Conference on Advanced Data Mining and Applications -- JUL 22-24, 2005 -- Wuhan, PEOPLES R CHINA
Keywords: multiagent systems; association rules; reinforcement learning; pursuit domain; data mining